The uses of the concept of culture in brazilian communication journals: a systematic literature review (Intercom - Brazilian Journal of Communication Sciences, 2023)
This article examines how the concept of culture is used in 148 scientific papers of Communication Sciences published between 2017 and 2021 in 30 Brazilian journals. To this end, a Systematic Literature Review and Content Analysis were carried out with a quantitative-qualitative methodological approach. In addition, the KH Coder software was used. A broad lack of conceptual delimitation was detected, as well as the use of culture for the composition of derived concepts. Identity and consumption are the most frequently used concepts in conjunction with culture. The reference made to cultural studies as the hegemonic current for the conceptualization of culture in communication research today also stands out.
Keywords: Culture; Communication; Systematic Literature review; Content analysis; Cultural Studies; HK Coder